2018
DOI: 10.3892/or.2018.6280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of HURP in non‑small cell lung cancer

Abstract: Previous studies have revealed that HURP (also known as DLGAP5 or KIAA0008) is overexpressed in many types of human cancers, such as hepatocellular carcinoma, squamous cell bladder cancer, and transitional cell carcinoma, indicating that HURP is a putative oncoprotein that promotes carcinogenesis through various molecular mechanisms. However, the role of HURP in the pathogenesis of non-small cell lung cancer (NSCLC) has not been reported. In the present study, we investigated the prognostic value of HURP among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…DLGAP5, a microtubule-associated protein, is phosphorylated by Aurora kinase A (AURKA) (43). In addition, DLGAP5 upregulation is associated with poor prognosis of patients with colorectal cancer (44), lung cancer (10), bladder cancer (11) and prostate cancer (12), indicating that DLGAP5 plays an important role in cancer prognosis. Branchi et al (44) reported that DLGAP5 was associated with the nodal status, and high DLGAP5 expression levels were associated with a less favorable overall survival rate in distinct molecular colorectal cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DLGAP5, a microtubule-associated protein, is phosphorylated by Aurora kinase A (AURKA) (43). In addition, DLGAP5 upregulation is associated with poor prognosis of patients with colorectal cancer (44), lung cancer (10), bladder cancer (11) and prostate cancer (12), indicating that DLGAP5 plays an important role in cancer prognosis. Branchi et al (44) reported that DLGAP5 was associated with the nodal status, and high DLGAP5 expression levels were associated with a less favorable overall survival rate in distinct molecular colorectal cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The human discs large-associated protein 5 (DLGAP5) gene, which is mapped to chromosome 14q22.3, is a cell cycle regulator involved in carcinogenesis (9). Wang et al (10) reported that DLGAP5 was upregulated in non-small cell lung cancer (NSCLC) and was associated with a shorter survival time. In cytological experiments, the knockdown of DLGAP5 caused inhibition of proliferation, migration and invasion of NSCLC cells (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, its high level of expression had a negative impact on the progression-free survival (HR=2.71) as well as on the overall survival (HR=1.75) in NSCLC. High levels of HURP expression in the IHC studies also correlated with a higher clinical stage and grade (43).…”
Section: Revision Of Novel Prognostic Factors In Lung Cancermentioning
confidence: 71%
“…The combination of paclitaxel and platinum drugs is a recognized first-line chemotherapy regimen for the treatment of advanced NSCLC. 6 However, the NCCN Clinical Practice Guidelines in Oncology for NSCLC recommend conventional treatment options without clarifying the specific details, such as the times of administration, cycles of chemotherapy, and doses of paclitaxel in combination with platinum drugs, and thus may cause great differences between different paclitaxelplatinum regimens in clinical practice. Of particular concern is that the efficacy and safety of a paclitaxel-platinum regimen may not be identical in different populations.…”
Section: Introductionmentioning
confidence: 99%